Outcome after Temporal Lobectomy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
Thirty seven patients, ages 7 to 18 years, who underwent temporal lobectomy for intractable seizures at the Mayo Clinic, Rochester, MN, between 1970 and 1983, were followed for a mean of 19 years (range 4 - 27 years).